2022
DOI: 10.1097/eja.0000000000001735
|View full text |Cite
|
Sign up to set email alerts
|

Randomised comparison between superior trunk and costoclavicular blocks for arthroscopic shoulder surgery

Abstract: BACKGROUND Superior trunk block (STB) provides noninferior analgesia to the interscalene block and reduces the risk of hemidiaphragmatic paralysis (HDP). Recently, supraclavicular spreading has also been shown to occur during costoclavicular block (CCB), presenting as an alternative analgesic technique for shoulder surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
(64 reference statements)
0
11
0
Order By: Relevance
“…However, the promising results of CCB in shoulder surgery do not seem to be reliably reproduced in our clinical experience [6]. In our previous report, the analgesic efficacy of CCB was not consistent, and a few patients required rescue blockades due to severe pain immediately after surgery.…”
Section: Introductionmentioning
confidence: 58%
See 1 more Smart Citation
“…However, the promising results of CCB in shoulder surgery do not seem to be reliably reproduced in our clinical experience [6]. In our previous report, the analgesic efficacy of CCB was not consistent, and a few patients required rescue blockades due to severe pain immediately after surgery.…”
Section: Introductionmentioning
confidence: 58%
“…In a preliminary analysis of our previous study [6], it was observed that approximately 70% of the patients reported a pain score greater than 0 at rest 1 h postoperatively after CCB when 20 ml of local anesthetic was used. We expected that using 40 ml of local anesthetic would demonstrate the incidence of any pain by up to 20%.…”
Section: Discussionmentioning
confidence: 98%
“…Among the 414 patients in the RCTs, 203 and 211 patients underwent CCB and other BPB techniques, respectively. The other BPB techniques included supraclavicular block (n = 3) [ 6 , 7 , 29 ], interscalene block (n = 1) [ 27 ], lateral sagittal block (n = 1) [ 26 ], superior trunk block (n = 1) [ 28 ], and paracoracoid block (n = 1) [ 8 ]. Table 1 shows detailed information regarding the seven included studies.…”
Section: Resultsmentioning
confidence: 99%
“…The incidence of HDP was significantly lower in the CCB group than in the other BPB group (5.9% vs. 31.3%, six studies; RR: 0.21, 95% CI [0.12, 0.36], P < 0.001, I 2 = 47%; fixed-effect model) ( Fig. 4 ) [ 6 8 , 26 28 ]. The re-estimated RR in the sensitivity analysis retained statistical significance ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation